HIV/AIDS Young Adult with Diabetes Mellitus Presenting with Newly Diagnosed Pulmonary Tuberculosis, Pneumonia Hypokalemia and Atrial Fibrillation : A Rare Case Report - Hesti Andika Putri; Reza Febryan (Al Makki Publisher, 2025)
Pneumonia, pulmonary tuberculosis (TB), Human Immunodeficiency Virus (HIV)/Acquired Immunodeficiency Syndrome (AIDS), and metabolic disorders such as diabetes mellitus (DM) represent complex clinical challenges, particularly in young adults. Hypokalemia and cardiac arrhythmias such as atrial fibrillation (AF) may further worsen the prognosis in these conditions. Recent studies have highlighted the association between TB, pneumonia, and AF, suggesting an increased risk of systemic inflammation and electrolyte disturbances. We report and analyze a rare case of a young male patient with a unique combination of HIV infection, diabetes mellitus, clinical pulmonary TB, pneumonia, hypokalemia, and atrial fibrillation. This is a descriptive case report study. Data were collected through history taking, physical examination, supporting investigations, and management during hospitalization. A 25-year-old male presented with shortness of breath for one day, a history of cough for more than three months, weight loss, fever, and a history of insulin use five years prior. Physical examination revealed pale conjunctiva and oral candidiasis; no other abnormalities were found. Laboratory tests showed hemoglobin 10.8 g/dL, leukocytes 8,280/µL, platelets 296,000/µL, MCV 89.4 fL, MCHC 33.9 g/dL, HbA1c 8.4%, potassium 2.7 mmol/L, lymphocytes 6.6%, and reactive results for HIV qualitative testing (R1, R2, R3). Electrocardiogram (ECG) showed atrial fibrillation with normal ventricular response. Chest X-ray revealed normal cardiac size and findings suggestive of bronchitis and suspected pneumonia. Thoracic CT scan with and without contrast demonstrated features consistent with pneumonia and multiple bilateral paratracheal and subcarinal lymphadenopathy. This case highlights the need for multidisciplinary management involving anesthesiology, pulmonology, internal medicine, cardiology, and pharmacy to ensure comprehensive care and optimize clinical outcomes, while preventing potentially fatal complications.